Perspectives of Young Digital Natives on Digital Marketing: Exploring Annoyance and Effectiveness with Eye-Tracking Analysis - Stefanos Balaskas; Georgia Kotsari; Maria Rigou (Future Internet, 2024)
Currently, there are a wide range of approaches to deploying digital ads, with advanced technologies now being harnessed to craft advertising that is engaging and even tailored to personal interests and preferences, yet potentially distracting and irritating. This research seeks to evaluate contemporary digital advertising methods by assessing how annoying they are to users, particularly when they distract users from intended tasks or cause delays in regular online activities. To pursue this, an eye-tracking study was conducted, with 51 participants navigating a specially designed website featuring seven distinct types of advertisements without a specific content to avoid the effect of ad content on the collected data. Participants were asked to execute specific information-seeking tasks during the experiment and afterwards to report if they recalled seeing each ad and the degree of annoyance by each ad type. Ad effectiveness is assessed by eye-tracking metrics (time to first fixation, average fixation duration, dwell time, fixation count, and revisit count) depicting how appealing an ad is as a marketing stimulus. Findings indicated that pop-ups, ads with content reorganization, and non-skippable videos ranked as the most annoying forms of advertising. Conversely, in-content ads without content reorganization, banners, and right rail ads were indicated as less intrusive options, seeming to strike a balance between effectiveness and user acceptance.